2021
DOI: 10.1001/jamanetworkopen.2021.11176
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Learning Model to Quantify Interstitial Fibrosis and Tubular Atrophy From Kidney Ultrasonography Images

Abstract: IMPORTANCE Interstitial fibrosis and tubular atrophy (IFTA) is a strong indicator of decline in kidney function and is measured using histopathological assessment of kidney biopsy core. At present, a noninvasive test to assess IFTA is not available. OBJECTIVE To develop and validate a deep learning (DL) algorithm to quantify IFTA from kidney ultrasonography images. DESIGN, SETTING, AND PARTICIPANTS This was a single-center diagnostic study of consecutive patients who underwent native kidney biopsy at John H. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The ability of ultrasound-based prediction of kidney interstitial fibrosis and tubular atrophy using a deep learning framework was also demonstrated in a diagnostic evaluation of 6,135 images in a study by Athavale et al, and the accuracy at the patient level was approximately 90% (35).…”
Section: Ckdmentioning
confidence: 85%
See 1 more Smart Citation
“…The ability of ultrasound-based prediction of kidney interstitial fibrosis and tubular atrophy using a deep learning framework was also demonstrated in a diagnostic evaluation of 6,135 images in a study by Athavale et al, and the accuracy at the patient level was approximately 90% (35).…”
Section: Ckdmentioning
confidence: 85%
“…Early and noninvasive detection is crucial to preventing or delaying the progression of CKD. In this systematic review, 12 studies were identified in this section, of which 10 referred to CKD and related diseases classification or screening (31)(32)(33)(34)(35)(36)(37)(38)(39)48) and two referred to complications after allograft renal transplantation (8,40). Iqbal et al showed that texture feature obtained from the cortex region in ultrasound images was more significant than those obtained from the entire kidney or renal medulla in distinguishing between normal and CKD patients (48).…”
Section: Ckdmentioning
confidence: 99%
“…Nowadays, there are an increasing number of tools to generate the segmentation of the entire WSIs [ 20 ], such as HALO software [ 21 ] and the PyTorch platform [ 22 , 23 ]. However, they require either GPU-based hardware or programming skills for researchers, which limits the promotion and application.…”
Section: Discussionmentioning
confidence: 99%
“…Results of routine histological analyses of renal biopsy tissues, such as light microscopic findings of formalin fixed paraffin embedded tissue sections, immunofluorescence staining for IgG, IgA, IgM, C1q, and C3c on fresh frozen tissue sections, and electron microscopic findings were collected from the patients’ medical charts in our hospital. Regarding the light microscopic findings, in addition to the usual evaluation items such as glomerular global sclerosis rate and crescent formation rate, we also evaluated the interstitial fibrosis and tubular atrophy (IFTA) score as the chronic histological change using the previously reported grading scale of 1–4 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%